Enrollment Motivations, Career Perceptions, and Preferences of Pharmacy Students under a Changing Educational Landscape: An Exploratory Survey at a Single Institution in South Korea - Youran Noh; Kyung-Bok Son (BMC Medical Education)
Abstract Background Pharmacy education in South Korea has undergone reforms aimed at diversifying student backgrounds and expanding professional roles. This study investigates students’ enrollment motivations, career perceptions, and career preferences at a single institution that admits cohorts under both the two-plus-four-year and six-year integrated systems. Methods A web-based survey was conducted among all enrolled students at a college of pharmacy in South Korea. Respondents were classified into two main groups: new admissions and transfer students. The new admissions group consisted of students admitted through early and regular admissions under the six-year integrated program. The transfer group included those who entered the college through the previous two-plus-four-year program. Descriptive statistics and logistic regression were used to analyze differences in enrollment motivations and career preferences. Results Of the 189 students, 118 completed the questionnaire, yielding a response rate of 62.43%. Economic stability—particularly income and job security—was the primary motivation for entering pharmacy school, but post-graduation preferences were influenced by broader factors. Community pharmacy emerged as the most preferred career path, driven by perceptions of lower workload, job security, and favorable working conditions. Preference for careers in community pharmacy shifted over time—being initially associated with male students and those admitted through regular admission, and later with students who had delayed enrollment. Admission type also played a significant role in shaping career preferences. Conclusions The strong preference for community pharmacy reflects not only its perceived benefits but also limited exposure to alternative career paths. Variations by admission type underscore the influence of student background on career trajectories. To foster greater career diversity and fulfill the goals of educational reform, pharmacy schools should expand curricular exposure to careers outside of community pharmacy and implement inclusive admissions strategies that attract students with diverse experiences.